Biblical reasoning : christological and trinitarian rules for exegesis - Jamieson, R. B., 1986-; Wittman, Tyler (Grand Rapids, MI. Baker Academic, 2022)
"Two experts in exegesis and dogmatics show how Christology and the Trinity are grounded in Scripture and how knowledge of these topics is critical for exegesis"--
Includes bibliographical references (pages 243-265) and indexes.
Keywords: Jesus Christ -- Person and offices; Bible -- Criticism, interpretation, etc; Bible -- Theology; Trinity